Telemedicine Across the Cancer Care Continuum: Evidence and Opportunities for Clinical Care, Research, and Policy. Issue 2 (March 2022) - Nekhlyudov, Larissa; Fleisher, Lee A.; Jacobsen, Paul B.
Abstract : Abstract: In this commentary, we provide an overview about the surge of telemedicine services during the COVID-19 pandemic, describe the cancer care continuum and existing evidence regarding the use of telemedicine across the continuum, and offer our perspective on existing opportunities to advance the use of telemedicine in clinical care, research, and policy. While research implications are relevant to an international audience, our focus pertains specifically to health care delivery and policy in the United States.